Performance of ’Rocha’ and ’Santa Maria’ pears as affected by planting density - Pasa, Mateus da Silveira; Fachinello, José Carlos; Rosa Júnior, Horacy Fagundes da; De Franceschi, Émerson; Schmitz, Juliano Dutra; Souza, André Luiz Kulkamp de (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to evaluate the performance of ’Rocha’ and ’Santa Maria’ pears at two planting densities. The experiment was carried out during the 2011/2012, 2012/2013, and 2013/2014 growing seasons, in one‑year‑old orchards (2011/2012) of ’Rocha’ and ’Santa Maria’ pears, trained in a central‑leader system and planted in two densities (2,000 and 4,000 trees per hectare). The assessed parameters were: production per hectare, production per tree, yield efficiency, number of fruit per tree, average fruit weight, trunk diameter increment, fruit firmness, and soluble solid contents. The cumulative yield of ’Rocha’ is greater at the higher planting density, whereas the yield efficiency of ’Santa Maria’ increases at the lower planting density, as the trees get more mature. Trunk diameter of ’Rocha’ also increases at the lower planting density. However, fruit quality parameters in both cultivars are little affected by planting density.